Identification of vacant land in Tegal Regency using cnn algorithm based on goolge earth imagery - Andriani, Wresti; Fatkhurrohman, Fatkhurrohman; Gunawan, Gunawan (Journal of Intelligent Decision Support System (IDSS), 2024)
This research developed a Convolutional Neural Network (CNN) algorithm to identify vacant land in Tegal Regency using imagery from Google Earth. By utilizing labeled imagery datasets, CNN models are optimized to recognize texture characteristics, colors, and distribution patterns of vacant land. Preprocessing and image sharing techniques are applied to improve model quality. The results of this study offer a new methodology in visual data processing for accurate and efficient identification of vacant land, providing a solid basis for more sustainable and efficient land use policies. This research contributes significantly to the scientific literature and field practice, particularly in natural resource management and regional planning